Voiding Disorders in Patients with Cerebrovascular Accident (Bangladesh Journal of Urology, 2020)
Background: Cerebrovascular accident often happens in elderly group, frequently causing voiding dysfunction. The aim of the study was to determine the magnitudes of various types of voiding disorders among patients of cerebrovascular accidents attending in Dhaka Medical College Hospital.Methods: It was a cross-sectional study conducted at the department of Urology ofDhaka Medical College Hospital from July 2009 to June 2011. Hundred and eight patients were enrolled in the study.Results: More than 61% subjects were male (n=66).Leading number of patients (45.4%) had three to six months disease duration. In this group 67.3% had overactive bladder, 64.7% had underactive bladder and 24.5% had normal activity of bladder. In patients with irritative symptoms majority had overactive bladder (71.4%) while in patients with obstructive symptoms half of the subjects had overactive bladder (50.0%). Majority of the subjects with DM (71.4%) and HTN (82.6%) had overactive bladder. Seventy percent (n=) subjects with overactive bladder had arterial stroke while around 82% (n=) of the underactive bladder subjects had venous stroke. More than 85% subjects with underactive bladder and around 78% subjects with overactive bladder had infection.Conclusion: Voiding dysfunction is a common sequel of acute stroke and most of the patients with irritative symptoms and about half of the subjects with obstructive symptoms had overactive bladder. Diabetes mellitus, hypertension and arterial stroke were found to be associated with overactive bladder.Bangladesh Journal of Urology, Vol. 23, No. 2, July 2020 p.136-141